Single step gastric aspirate shake test as a screening procedure for predicting the risk of neonatal respiratory distress - H. Tjandra; E. Sarwono (Indonesian Pediatric Society, 1981)
Predicting the occurrence of Neonatal Respiratory Disttress or lRDS in peripheral areas before symptoms and signs develop is of utmost importance, since an appropriate treatment and management can be performed only in a well-equipped hospital. Many diagnostic methods are used for the prediction of IRDS, yet they require elaborate and sophisticated instruments and technical experts which usually are not available in the front-line medical centres.In this study, the single-step gastric aspirate shake test of Tanswell et al., (1977) proves to be all extremely valuable method which should be incorporated into the armamentarium of diagnostic tests in the first line medical centres, as to enable a more well-directed referral system.Despite the small number of our IRDS cases, our patients show clinical pictures similar to those observed by many other investigators. However, further studies for a more conclusive result are certainly justified.